Sense of Place among Adolescents: Factors Influencing the Place Attachment on Shopping Malls - Kusumowidagdo, Astrid; Rembulan, Cicilia Larasati; Sachari, Agus (Makara Human Behavior Studies in Asia, 2015)
This research aims to find the push factors that create relationships between youth and shopping centers and examines how different mall environments also help create different emotional bonds towards the malls. This topic is further observed with an explorative study that obtained its primary data from interviews and secondary data from various supporting literatures as well as from a number of observations. The informants were 15 visitors of each of the following shopping centers: Tunjungan Plaza and Ciputra World in Surabaya; and Mal Ciputra and Gandaria City in Jakarta. The total informant number is 60. The research found several affective factors that support the formation of place attachment: physical factors that lead to indirect place attachment, social factors or social interactions that happen in the shopping center, cultural factors, personal factors (including gender, race and ethnicity), memories and experience, place satisfaction, interaction and activity features, and time factor. The different age of shopping centers also had an effect to the factors present.